2023
DOI: 10.3390/ijerph20032162
|View full text |Cite
|
Sign up to set email alerts
|

How Does Problematic Internet Use Influence Chinese Rural Adolescent Externalizing Problem Behaviors? The Mediating Role of Mental Health and the Moderating Role of Parental Knowledge

Abstract: This study aims to provide a new perspective on the relationship between problematic Internet use and externalizing problem behavior among adolescents. Many studies have focused on the relationship between problematic Internet use and adolescent externalizing problem behavior; however, research on the underlying mechanism remain understudied. Altogether, 1116 Chinese rural adolescents aged 13–17 years completed a self-report questionnaire. The results indicate that: (1) Problematic Internet use has a negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…Problematic social media use, instead, would not seem to be a putative transdiagnostic factor, but rather a dimension-specific factor, as it emerged to be involved in the path from emotion dysregulation to externalizing problems only. This evidence extends beyond the results by Yang and Zhu [ 84 ], which showed that problematic Internet use played a significant role in fostering adolescent externalizing problems. The mediating role of problematic social media use in the relation between emotion dysregulation and externalizing problems could be understood by considering that using social media offers immediate gratification and relief from negative affective states, thus potentially representing a means of emotion regulation.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Problematic social media use, instead, would not seem to be a putative transdiagnostic factor, but rather a dimension-specific factor, as it emerged to be involved in the path from emotion dysregulation to externalizing problems only. This evidence extends beyond the results by Yang and Zhu [ 84 ], which showed that problematic Internet use played a significant role in fostering adolescent externalizing problems. The mediating role of problematic social media use in the relation between emotion dysregulation and externalizing problems could be understood by considering that using social media offers immediate gratification and relief from negative affective states, thus potentially representing a means of emotion regulation.…”
Section: Discussionsupporting
confidence: 81%
“… High emotion regulation difficulties were directly related to high levels of internalizing and externalizing problems [ 45 , 54 ], as well as to high levels of boredom [ 11 , 81 ] and problematic social media use [ 37 , 80 , 87 ]; High levels of boredom and problematic social media use predicted high levels of internalizing and externalizing problems [ 33 , 49 , 69 , 84 ]. …”
Section: Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations